Factors influencing livestock price changes in Kelantan - Abdullah Fahmi Shaari, . (2012)
The problem in this research is about increasing the livestock price in certain time. That’s phenomena show that livestock price in Kelantan not have a stability price even the government stated about the ceiling price. The objective of this study is to determine whether demand or supply is influencing the rising of the livestock price. This research was conducted in order to define factors that lead to livestock rising. Qualitative methods are using in this research by interview the farmer and sellers of livestock. From previous studies, many researchers agree that the supply and demand is a major factor in the livestock price changes. 20 respondents are chosen from farmers and sellers of livestock have been interview to find out the factors that motivate them in the pricing of livestock products. The study also aims to seek the opinion of the livestock farmers and sellers of livestock are to define effective solutions for this problem. Variables used in this study are the 'demand' and 'Selling'.Results from this study prove that the supply and demand factors are the cause of the problem in increase livestock price. The recommendations by the farmers and sellers they hope the government or any agencies try to create a local pallet to avoid dependence on imports pallets. Hoped that this study will help the Government of Malaysia in define an exact solution for this phenomenon in the future and make it relevant for all parties